Ghrelin Receptors in Non-Mammalian Vertebrates - Kaiya, Hiroyuki (Frontiers Media S.A., 2013)
The growth hormone secretagogue-receptor (GHS-R) was discovered in humans and pigs in 1996. The endogenous ligand, ghrelin, was discovered 3 years later, in 1999, and our understanding of the physiological significance of the ghrelin system in vertebrates has grown steadily since then. Although the ghrelin system in non-mammalian vertebrates is a subject of great interest, protein sequence data for the receptor in non-mammalian vertebrates has been limited until recently, and related biological information has not been well organized. In this review, we summarize current information related to the ghrelin receptor in non-mammalian vertebrates.